Advanced MRI Protocols to Discriminate Glioma From Treatment Effects: State of the Art and Future Directions - Malik, Dania G.; Rath, Tanya J.; Urcuyo Acevedo, Javier C.; Canoll, Peter D.; Swanson, Kristin R.; Boxerman, Jerrold L.; Quarles, C. Chad; Schmainda, Kathleen M.; Burns, Terry C.; Hu, Leland S. (Frontiers in Radiology, 2022)
In the follow-up of treated high-grade gliomas (HGG), differentiating true tumor progression from treatment-related effects such as pseudoprogression and radiation necrosis presents an ongoing clinical challenge. Conventional MRI with and without intravenous contrast serves as the clinical benchmark for post-treatment surveillance imaging of HGG. However, many advanced imaging techniques have shown promise in helping better delineate findings in indeterminate scenarios, as post-treatment effects can often mimic true tumor progression on conventional imaging. These challenges are further confounded by the histologic admixture that can commonly occur between tumor growth and treatment-related effects within the post-treatment bed. This review discusses the current practices in surveillance imaging of HGG and the role for advanced imaging techniques, including perfusion MRI and metabolic MRI.